2022
DOI: 10.21273/hortsci16763-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses for Leaf Variegation in Hybrid Grape Populations (Vitis spp.) Reveals Two Loci, Lvar1 and Lvar2

Abstract: Variegation in Vitis hybrids was investigated to confirm the inheritance as a single, recessive gene as previously proposed and commonly observed in breeding programs. Variegated leaves have ornamental appeal, but the phenotype is sublethal in some environments. Twenty-nine grape families were characterized for variegation including F1, S1, and S2 populations. The majority segregated 3 wild type (WT):1 variegated and were supported by chi-square tests. Four populations had segregation ratios supporting 15:1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In grapevine, Reisch and Watson (1984) were the first to propose the expression of a nuclear recessive gene var to account for the leaf variegation. Further studies in grapevines developed by Olson et al (2022) demonstrated that the variegated phenotype was related to the expression of two nuclear recessive genes Lvar1 and Lvar2. It is possible that the variegation observed in 'Variegada' could be related to the expression of a recessive gene.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…In grapevine, Reisch and Watson (1984) were the first to propose the expression of a nuclear recessive gene var to account for the leaf variegation. Further studies in grapevines developed by Olson et al (2022) demonstrated that the variegated phenotype was related to the expression of two nuclear recessive genes Lvar1 and Lvar2. It is possible that the variegation observed in 'Variegada' could be related to the expression of a recessive gene.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…Especially the experimental work on variegation mutants in Arabidopsis thaliana helped us better understand the underlying mechanisms [ 1 , 5 22 ]. Other leaf variegation studies were carried out on tomato [ 23 33 ], and studies on Arum italicum [ 34 ], barley [ 35 ], Brassica napus [ 36 ], Camellia sinensis [ 37 , 38 ]; Grapevine [ 39 ], Ilex X altaclerensis [ 20 , 21 ], Lotus japonicus [ 20 ], Epipremnum aureum [ 40 ], tobacco [ 41 ], Hedera helix [ 42 ], Vigna radiata [ 43 ] and Zea mays [ 44 ].…”
Section: Introductionmentioning
confidence: 99%